Signaling in Plant-Microbe Interactions - Baker, B.; Zambryski, P.; Staskawicz, B.; Dinesh-Kumar, S.P.
Analysis of viral and bacterial pathogenesis has revealed common themes in the ways in which plants and animals respond to pathogenic agents. Pathogenic bacteria use macromolecule delivery systems (types III and IV ) to deliver microbial avirulence proteins and transfer DNA-protein complexes directly into plant cells. The molecular events that constitute critical steps of plant-pathogen interactions seem to involve ligand-receptor mechanisms for pathogen recognition and the induction of signal transduction pathways in the plant that lead to defense responses. Unraveling the molecular basis of disease resistance pathways has laid a foundation for the rational design of crop protection strategies.